2018
DOI: 10.7754/clin.lab.2018.180138
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Human Papillomavirus E6/E7 mRNA Detection in Screening for Cervical Cancer in Women Positive for Human Papillomavirus DNA or

Abstract: Background: The detection of human papillomavirus (HPV) E6/E7 mRNA indicates a risk of further deterioration in cervical lesions. We explored the clinical value of HPV E6/E7 mRNA detection in cervical cancer screening in women positive for HPV or with abnormal thin-prep cytology test (TCT) results in the Xinjiang region of China. Methods: A total of 6,800 women were screened in our hospital for cervical cancer by both TCT and HPV DNA testing from August 2013 to June 2015. Of these, 197 had abnormal cytological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
4
1
Order By: Relevance
“…Consequently, this results in overexpression of the two oncogenes which become useful in evaluating risk of cervical carcinogenesis. This consensus is supported by studies included in our review showing that HPV E6/E7 mRNA assays have diagnostic relevance for CIN2+ with sensitivity, specificity, PPV, NPV, and AUC ranges of 65-100%, 42.7-90.2%, 10-85.9%, 66.7-100%, and 0.59-0.80, respectively, [13,29,32,33]. However, due to the heterogeneity of participants in the included studies, the results of HPV E6/E7 mRNA test performance have limited generalizability.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Consequently, this results in overexpression of the two oncogenes which become useful in evaluating risk of cervical carcinogenesis. This consensus is supported by studies included in our review showing that HPV E6/E7 mRNA assays have diagnostic relevance for CIN2+ with sensitivity, specificity, PPV, NPV, and AUC ranges of 65-100%, 42.7-90.2%, 10-85.9%, 66.7-100%, and 0.59-0.80, respectively, [13,29,32,33]. However, due to the heterogeneity of participants in the included studies, the results of HPV E6/E7 mRNA test performance have limited generalizability.…”
Section: Discussionsupporting
confidence: 63%
“…The diagnostic performance of each of the assays as compared with histologically confirmed high-grade cervical intraepithelial neoplasia (CIN2+) as an endpoint was as follows; 1) HPV E6/E7 mRNA test performance varied considerably depending on the diagnostic method used as shown in Table 1. Eight of the studies included recorded a sensitivity, specificity, PPV, NPV, and Area Under Receiver Operating Characteristic Curve (AUC) ranges of 65-100%, 42.7-90.2%, 10-85.9%, 66.7-100%, and 0.59-0.80, respectively, using liquid based cytology (LBC) samples majorly on QuantiVirus®HPV platform [13,29,[32][33][34][35][36][37]. 2).…”
Section: Diagnostic Performance Of the Listed Assays To Detect Cin2+mentioning
confidence: 99%
“…However, our result was lower than that of samples with abnormal cytological outcomes collected at the Affiliated Hospital of Xinjiang Medical University [ 25 ]. In addition, this study showed that the cervical cancer detection rate was 1.48%, which was higher than that reported by Husaiyin et al (who conducted cervical cancer examinations in Pishan County) [ 26 ] and by Han et al (whose study was conducted in Urumqi) [ 27 ]. Different sample sources could account for these inconsistencies.…”
Section: Discussioncontrasting
confidence: 66%
“…Our review result is in line with this argument. On top of this, the reported AU-ROC curve by six of the articles [51,[58][59][60][61][62] Burger et al [63] review on HPV mRNA tests for the detection of cervical intraepithelial neoplasia reported sensitivities between 41 and 86% and 90-95% for the PreTect Proofer/Easy Q and APTIMA assay, respectively. Similarly, the reported specificities vary from 63 to 97% and 42-61% for the PreTect Proofer/Easy Q and APTIMA assay, respectively.…”
Section: Discussionmentioning
confidence: 99%